The Marketing Activities in Royal Monasteries Affecting Repeat Making Merit Intention of Thai Generation Y Tourists - Run, Pharatt; Laksitamas, Prin (Journal of Cultural Approach, 2021)
The purposes of this research were aimed to study 1) The fundamental characteristics of Thai generation Y tourists and 2) The opinion level of the marketing activities in royal monasteries affecting repeat making merit intention of Thai generation Y tourists. The data was collected from the samples of Thai generation Y tourists who visited Wat Rai Khing. This research used mixed research, by conducted interviews and used questionnaires to collect data from 400 samples. The data were analyzed using frequency distribution, percentage, arithmetic means, and standard deviation. The responded samples of Thai generation Y tourists were mostly female, aged 21 – 25 years old, single status, Lower than a bachelor degree, work in private companies, average income per month is less than or equal 15,000 baht, stayed in the central region, the reason for visited the monastery was intended to join activities of the royal monastery, the monastery was visited known from friends/acquaintances, the ways of traveling was by self and experience of traveling was over 3 times The results of the study showed that the opinion level of Thai generation Y tourists on marketing activities in royal monasteries was at the middle-level ( = 3.16) by agreed at a high level in activities depending on the mind ( = 3.84). The repeated travel intention of Thai generation Y was at a high-level ( = 3.80). The important factor was to tell the others about the good experience of the marketing activities in royal monasteries ( = 3.87).